Distribution of phytoplankton chlorophyll continuously recorded in the JARE-25 cruise to Syowa Station, Antarctica (SIBEX I) - Taniguchi,Akira; Hamada,Etuyuki; Okazaki,Mihoko; Naito,Yasuhiko (1986)
P(論文) The attempt was made to record the geographical distribution of chlorophyll α on a finer scale over semi-global ranges. A prototype of continuous measuring-recording system was designed and built in icebreaker SHIRASE and rich data on chlorophyll distribution were collected on the JARE-25 cruise (1983/84) to Syowa Station in Antarctica. Diel variation of chlorophyll in the Antarctic Ocean was also documented. The results obtained confirm gross patterns of the geographical distribution and diel variation reported by many previous authors. Furthermore, several facts are newly found : e.g., relationships of chlorophyll to temperature are quite variable among different sea areas, diel variation is less intense in the coastal area where a 12-hour periodicity is influential, and occurrence of a certain hydrographic condition which enhances phytoplankton productivity in the area between the Agulhas Convergence and the Subtropical Convergence south of South Africa. departmental bulletin paper